1999
DOI: 10.1088/0953-8984/11/17/318
|View full text |Cite
|
Sign up to set email alerts
|

Far-infrared spectroscopy investigation of commensurate and incommensurate Cs2CdBr4crystal

Abstract: Far-infrared reflectivity measurements of Cs 2 CdBr 4 crystal were performed over the frequency region 15-600 cm −1 and temperature region 10-297 K. All transverse lattice modes have frequencies below 230 cm −1 because of the heavy atoms in the Cs 2 CdBr 4 crystal. A sequence of phase transitions can be identified on the basis of the activation of new modes below the phase transition temperatures due to the lowering of the crystal symmetry on cooling. Factor-group analysis was carried out and selection rules f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The requirements are a precise knowledge of all the normal mode frequencies and even their temperature evolution. In our case only some mode frequencies of Cs 2 CdBr 4 obtained from Raman and infrared spectroscopies are available in the literature [13,14,18], and up to now no neutron diffraction data have been reported. More recently, Shchur et al [24] reported normal mode data frequencies obtained by model calculations.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The requirements are a precise knowledge of all the normal mode frequencies and even their temperature evolution. In our case only some mode frequencies of Cs 2 CdBr 4 obtained from Raman and infrared spectroscopies are available in the literature [13,14,18], and up to now no neutron diffraction data have been reported. More recently, Shchur et al [24] reported normal mode data frequencies obtained by model calculations.…”
Section: Discussionmentioning
confidence: 92%
“…This phase transition sequence and the physical properties of the various phases have been studied by means of different experimental techniques which include dilatometry [10], dielectric [8,10], NQR [11,12], Raman scattering [13,14], ultrasonic [15,16], and x-ray diffraction [6,7,9,17] approaches. Two additional phase transitions at 208 K [8] and 130 K [17] are still under discussion [10,18]. More recently, the specific heat results obtained by AC calorimetry [19] have given some additional evidence for these new phase transitions.…”
Section: Introductionmentioning
confidence: 99%